Welding Training Flux Cored Arc Welding (FCAW) in Improving Welding Skills - Firman Husain (Collaborate Engineering Daily Book Series, 2023)
The connection method using welding has advantages compared to other methods, including better connection efficiency, can be used in constructions that work at high temperatures, and the results are neater. The connection resulting from the welding process is permanent, and the process is faster. However, the quality of welding results is strongly influenced by the skill and ability to weld welder. Therefore, welding training is very important to improve skills, so welding training is held for the community in Laok Jang-Jang Village, Arjasa District, Sumenep Regency, East Java Province. This training includes providing material on Occupational Health Safety (K3), basic FCAW welding, and welding practices. The training results showed an increase in the skills of the trainees, as seen from the welding results, which had no defects. This shows that the trainees have applied the material provided before carrying out Flux Cored Arc Welding (FCAW) welding processes.